Membangun Bisnis Digital Filtrize menggunakan Metode Project Based Learning - Algyon Faras; Nakula Bintang Nashwandra; Jauza Nadhifah; Wien Kuntari (Ebisnis Manajemen, 2024)
In the ever-evolving digital age, social media, especially Instagram, has become an important platform that not only serves as a communication tool, but also as an effective marketing tool. Instagram filters, as one of the main features, have evolved into an important creative and marketing tool for both individuals and businesses. Filtrize comes as a provider of Instagram filter creation services tailored to customer needs, with the aim of creating filters that are unique and in line with brand identity. However, in order to stay relevant and thrive amidst intense competition, Filtrize needs to adopt effective methods in its business development. One of the approaches used as a solution is the application of the Project Based Learning (PBL) method, which can integrate theory and practice in the development of this digital business. This research aims to explore how the application of the PBL method can be used to build and develop Filtrize's business. The methods used in this research include observation, literature study, and customer feedback to collect data on market trends, customer expectations, and product evaluation. The results of this research are expected to provide new insights into digital service business development in the creative field and produce a business model that is not only profitable, but also sustainable.